Sexuality of people with intestinal ostomy - Danyelle Braga Rodrigues Cardoso; Camilo Eduardo Almeida; Mary Elizabeth de Santana; Dione Seabra de Carvalho; Helena Megumi Sonobe; Namie Okino Sawada (Universidade Federal do Ceará, 2015)
Objective: to describe the experience of sexuality and other everyday life aspects for people with intestinal ostomy. Methods: qualitative, descriptive study with ten participants of the Specialized Reference Unit who gave interviews with inductive content analysis. Results: the established themes were Physical, emotional and socio-cultural changes, Changes in the exercise of sexuality of people with intestinal ostomy and Importance of the interdisciplinary support of the new sexuality. These changes are linked to body image, the self-esteem and interpersonal relationships with the partner, family and friends, going beyond the visible with the emergence of fear, rejection, difficulty with new relationships, body shame, embarrassment by the collector equipment, fear of the sexual act causes damage to the stoma and difficult to talk about the condition. Conclusion: the ostomy condition requires adaptation process, requiring trained interdisciplinary team in physiological and psychosocial problems resulting from surgical and therapeutic adjuvant treatment, which hinder the sexuality of these individuals.